Democratically binding - Goodin, Robert E. (Oñati Socio-Legal Series, 2011)
The aspiration of the 'Democracy Unbound' project was to extend democracy in two dimensions: range and scope. The former would give a wider range of people the vote. The latter would give people a wider scope of things to vote on. In practice, no doubt there is room to do much more of both. But whereas it would be democratically justifiable in an ideal world for democracy to be completely unbounded as regards range, even in an ideal world democracy ought be subject to some limits internal to the logic of democracy itself as regards its scope.